Incidence of pressure injury and nursing care time in intensive care - Mohamed Ali, Yasmin Cardoso Metwaly; Souza, Taís Milena Milena Pantaleão; Garcia, Paulo Carlos; Nogueira, Paula Cristina (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objectives: To correlate the incidence of pressure injury (PI) with the average time of nursing care in an intensive care unit (ICU). Method: Epidemiological, observational, retrospective study, carried out in the ICU of a university hospital. Data were collected by consulting the PI incidence and the average nursing care time from ICU databases between 2010 and 2014. Measures of central tendency and variability, and Pearson’s correlation coefficient were used for data analysis. Results: The average incidence of PI between 2010 and 2014 was 10.83% (SD = 2.87) and the average time spent in nursing care for patients admitted to the ICU was 15 hours (SD = 0.94). There was no statistically significant correlation between the incidence of PI and the nursing care time (r = -0.17; p = 0.199), however, the results suggested an overload on the nursing team. Conclusion: This study confirms the importance of implementing and reassessing the effectiveness of preventive care protocols for PI, in addition to warning about the work overload of nursing in assisting critically ill patients.